The “Slow Horse Racing Effect” on Lung Function in Adult Life in Chronic Obstructive Pulmonary Disease Associated to Biomass Exposure - Ramírez-Venegas, Alejandra; Montiel-Lopez, Francisco; Falfan-Valencia, Ramces; Pérez-Rubio, Gloria; Sansores, Raúl H (Frontiers in Medicine, 2021)
Although different trajectories in lung function decline have been identified in patients with COPD associated to tobacco exposure (TE-COPD), genetic, environmental, and infectious factors affecting lung function throughout life have not been fully elucidated in patients with COPD associated to biomass (BE-COPD). In this review, we present current epidemiological findings and notable advances in the natural history of lung decline in BE-COPD, as well as conditions modeling the FEV1 trajectory, such as health insults, during the first years of childhood. Evidence shows that women exposed to biomass smoke reach adult life with a lower FEV1 than expected. However, in contrast to the “horse racing effect” predicting an excessive lung-function decline in forthcoming years, as observed in smokers, this decline is slower in nonsmokers, and no rapid decliners are observed. Accordingly, BE-COPD might be considered another phenotype of COPD based on assessments of lung function decline. Likewise, other functional and clinical aspects described in this review suggest that this condition might be similar to TE-COPD. More research is needed to fully characterize this subgroup of variants of COPD.